2018
DOI: 10.2298/jsc170721101l
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing an electrochemical oxidation process using artificial neural network, genetic algorithm and particle swarm optimization

Abstract: This study proposes a novel hybrid of artificial neural network (ANN), genetic algorithm (GA), and particle swarm optimization (PSO) to model and optimize the relevant parameters of an electrochemical oxidation (EO) Acid Black 2 process. The back propagation neural network (BPNN) was used as a modelling tool. To avoid over-fitting, GA was applied to improve the generalized capability of BPNN by optimizing the weights. In addition, an optimization model was developed to assess the performance of the EO process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The R 2 values indicated that the variable range of independent variables could explain 82.53% and 96.20 % of the changes in the corresponding COPs yield by RSM and ANN models, respectively. Compared with RSM model, the superiority of ANN model has been previously confirmed by many reports [37] , [38] . Therefore, ANN modeling method was selected to optimize the subsequent polysaccharides process in this study.…”
Section: Resultsmentioning
confidence: 74%
“…The R 2 values indicated that the variable range of independent variables could explain 82.53% and 96.20 % of the changes in the corresponding COPs yield by RSM and ANN models, respectively. Compared with RSM model, the superiority of ANN model has been previously confirmed by many reports [37] , [38] . Therefore, ANN modeling method was selected to optimize the subsequent polysaccharides process in this study.…”
Section: Resultsmentioning
confidence: 74%
“…8) of the standardized residual of the model is subject to normal distribution, which confirms that the ANN model has high accuracy to predict results. 38 Fig. 9, the maximum removal efficiency was obtained after 100 generations.…”
Section: Ann Modelling and Optimization Of Parametersmentioning
confidence: 88%
“…Support Vector Regression SVR is a regression technique rooted in Vapnik’s concept of support vector. SVR is a kernel-based technique with a solid theoretical basis and is generally easier to implement than artificial neural networks, its major competitor (Rupp 2015 ).SVR is a supervised-learning machine characterized by using Kernel functions, the number of support vectors, penalty parameters C, coefficient of non-sensitivity ε, and the Gaussian nucleus bandwidth σ (Liu et al 2018 ). These parameters can be manually defined or by the mean of heuristic optimization algorithms.…”
Section: Regression Methodsmentioning
confidence: 99%